2013
DOI: 10.1007/s10534-013-9608-4
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide (NO) counteracts cadmium induced cytotoxic processes mediated by reactive oxygen species (ROS) in Brassica juncea: cross-talk between ROS, NO and antioxidant responses

Abstract: Research on NO in plants has achieved huge attention in recent years mainly due to its function in plant growth and development under biotic and abiotic stresses. In the present study, we investigated Cd induced NO generation and its relationship to ROS and antioxidant regulation in Brassica juncea. Cd accumulated rapidly in roots and caused oxidative stress as indicated by increased level of lipid peroxidation and H2O2 thus, inhibiting the overall plant growth. It significantly decreased the root length, leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(58 citation statements)
references
References 68 publications
5
51
0
2
Order By: Relevance
“…In wheat roots, exogenous NO ameliorates Cd toxicity by attenuating Cd-induced ROS generation (Singh et al 2008). Similar results were observed in mustard, where NO counteracts Cdinduced cytotoxic processes mediated by ROS (Verma et al 2013). In both wheat and mustard, authors have reported that apart from the downregulation of ROS production NO decreased also stress response, including antioxidant enzymes.…”
Section: Introductionsupporting
confidence: 57%
“…In wheat roots, exogenous NO ameliorates Cd toxicity by attenuating Cd-induced ROS generation (Singh et al 2008). Similar results were observed in mustard, where NO counteracts Cdinduced cytotoxic processes mediated by ROS (Verma et al 2013). In both wheat and mustard, authors have reported that apart from the downregulation of ROS production NO decreased also stress response, including antioxidant enzymes.…”
Section: Introductionsupporting
confidence: 57%
“…First of all, NO could directly scavenge the overproduced ROS in cells. Secondly, NO might function as a signaling molecule to modulate antioxidative gene expression (Verma et al 2013). However, accumulating evidence shows that NO is a double edged sword in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Enzymatic and non-enzymatic antioxidants exhibit two classic patterns of endogenous protective mechanisms to prevent oxidative stress (35). Antioxidant enzymes, including SOD and GSH-Px, may clear accumulated OFR and associated metabolites to maintain homeostasis and attenuate the effects of ROS, thus protecting cellular structures from destruction and prevent the onset of fatigue (36). In the present study, TM treated female and male mice exhibited increased serum, hepatic and muscular SOD and GSH-Px, and decreased MDA and ROS levels to different degrees depending on the concentration of TM administered.…”
Section: Tm (G/kg) Tm (G/kg) ----------------------------------------mentioning
confidence: 99%